WILAYAH POTENSI IKAN PELAGIS PADA VARIASI KEJADIAN ENSO DAN NORMAL DI SELAT SUNDA - Nurkhairan, Yulianti; Supriatna, Supriatna; Susiloningtyas, Dewi (UI Scholars Hub, 2018)
Indonesia's geographical location resulted in the fisheries in the Sunda Strait also affected by global climate dynamics. One of them is the ENSO (El Nino-Southern Oscillation) phenomenon in the Pacific Ocean that affects the seasons and marine waters in Indonesia. The fishery in the Sunda Strait has a commodity of pelagic fish where potential area can be estimated from oceanographic parameters such as sea surface temperature (SST) and chlorophyll-a concentration in marine waters. The dynamics of the spatial and temporal parameter of oceanography due to the variation of ENSO phenomena can be identified from Aqua satellite images carrying the MODIS sensor. Information on potential areas of pelagic fish is needed to help the effectiveness of fishery activities and increase the production of capture fisheries. Monthly oceanographic parameters in the Sunda Strait are overlayed based on 4 seasonal variations in a year on each variation of the ENSO phenomenon and are classified by moderate, potential, and very potential classes. As a result, the potential areas of very potential pelagic fish in the Sunda Strait in the La Nina and El Nino phenomena are greater than in normal conditions and occur in the east seasons until the second transition. The spread is in the Indian Ocean to the west of the Sunda Strait.